HUBUNGAN KEMAMPUAN AKADEMIK MAHASISWA REKAM MEDIS DENGAN HASIL BELAJAR PADA MAHASISWA TINGKAT AKHIR - Wiranata, Tyansa Eka Sampoerna; Rumana, Nanda Aula; Widjaja, Lily; Putra, Daniel Happy (STKIP Pesisir Selatan, 2024)
This research aims to determine the relationship between student academic abilities and learning outcomes in final year students of the Medical Records and Health Information Study Program at one of the universities in Jakarta. The research method used is quantitative analysis using the independent T-test where researchers describe the relationship between students' academic abilities and learning outcomes. Based on the research results, it was found that the average age of students was 22 years with the majority of students being female, namely 77.8%. The description of academic ability is 88.9% good and 11.1% not good. The average learning outcome description is 3.51 with the largest learning outcome being 3.97 and the smallest being 2.66. Based on the research results, it was found that there was a significant relationship between learning outcomes and academic abilities (p-value <0.002). Where respondents whose academic abilities are good have a higher learning outcome score of 3.54 compared to respondents whose academic abilities are not good, namely 3.25. So, it can be seen that there is a quite significant correlation between academic ability and learning outcomes.